Optimization, evaluation and calibration of a cross-strip DOI detector. (20th February 2018) - Schmidt, F P; Kolb, A; Pichler, B J
Abstract: This study depicts the evaluation of a SiPM detector with depth of interaction (DOI) capability via a dual-sided readout that is suitable for high-resolution positron emission tomography and magnetic resonance (PET/MR) imaging. Two different 12  ×  12 pixelated LSO scintillator arrays with a crystal pitch of 1.60 mm are examined. One array is 20 mm-long with a crystal separation by the specular reflector Vikuiti enhanced specular reflector (ESR), and the other one is 18 mm-long and separated by the diffuse reflector Lumirror E60 (E60). An improvement in energy resolution from 22.6% to 15.5% for the scintillator array with the E60 reflector is achieved by taking a nonlinear light collection correction into account. The results are FWHM energy resolutions of 14.0% and 15.5%, average FWHM DOI resolutions of 2.96 mm and 1.83 mm, and FWHM coincidence resolving times of 1.09 ns and 1.48 ns for the scintillator array with the ESR and that with the E60 reflector, respectively. The measured DOI signal ratios need to be assigned to an interaction depth inside the scintillator crystal. A linear and a nonlinear method, using the intrinsic scintillator radiation from lutetium, are implemented for an easy to apply calibration and are compared to the conventional method, which exploits a setup with an externally collimated radiation beam. The deviation between the DOI functions of the linear or nonlinear method and the conventional method is determined. The resulting average of differences in DOI positions is 0.67 mm and 0.45 mm for the nonlinear calibration method for the scintillator array with the ESR and with the E60 reflector, respectively; Whereas the linear calibration method results in 0.51 mm and 0.32 mm for the scintillator array with the ESR and the E60 reflector, respectively; and is, due to its simplicity, also applicable in assembled detector systems.